The role of thyroid stimulating hormone in the timing of thyroxin supplement after thyroid operations - Basil Abdulrazzaq Saadallah Al-Khayyat (Al Muthanna University, 2021)
Thyroid Stimulating Hormone (TSH) levels can be measured accurately down to a very low serum concentration with an immunoassay. When the serum TSH level is in the normal range, measuring the T3 and T4 levels is redundant. The objective of this study is to study the relation of TSH levels postoperatively in thyroid surgeries with the timing for thyroxin treatment as a supplemental and suppressive therapy. A prospective cohort study was done on 84 patients underwent thyroid operations in Al-Yarmouk Teaching Hospital from March 2010 through November 2012. Patients underwent different thyroid operations (lobectomy, subtotal thyroidectomy and total thyroidectomy) for different thyroid pathology. Later, they were followed up by TSH assay in periods of 2, 4, 6 and 12 months postoperatively. Variables were compared by using the analysis of variance, ANOVA test. P – values equal or less than 0.05 and 0.01 were considered to be statistically significant and highly significant, respectively. The mean age of patients was 43.30 ± 10.19 years. The females made the vast majority of study sample (85.7%). Patients were divided into six groups: simple colloid goiters (17 patients), multinodular goiters (32 patients), solitary thyroid nodules (11 patients), Hashimoto’s thyroiditis (8 patients), Graves’ disease (8 patients) and papillary and follicular carcinomas (8 patients). The study revealed that all patients with malignant thyroid nodules (i.e. those with total thyroidectomies) and the vast majority of patients with Hashimoto’s thyroiditis were in definite need for thyroxin treatment post-operatively. Other patients were variable in their need and timing of treatment according to the histopathological results and the type of operations. In conclusion; measurement of TSH level postoperatively is a good indicator for need of thyroxin treatment and for dose adjustment with the help of pathological results and the type of surgery.